2017
DOI: 10.1371/journal.ppat.1006281
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus glycoprotein complex gH/gL/gO uses PDGFR-α as a key for entry

Abstract: Herpesvirus gH/gL envelope glycoprotein complexes are key players in virus entry as ligands for host cell receptors and by promoting fusion of viral envelopes with cellular membranes. Human cytomegalovirus (HCMV) has two alternative gH/gL complexes, gH/gL/gO and gH/gL/UL128,130,131A which both shape the HCMV tropism. By studying binding of HCMV particles to fibroblasts, we could for the first time show that virion gH/gL/gO binds to platelet-derived growth factor-α (PDGFR-α) on the surface of fibroblasts and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
173
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(186 citation statements)
references
References 58 publications
(130 reference statements)
13
173
0
Order By: Relevance
“…These data are well in line with previous reports showing the inhibitory capacity of sPDGFRα for several distinct HCMV strains (26). Notably, even at a concentration of 1.25μg/ml sPDGFRα we observed a residual infectivity of about 1 - 2% in epithelial cells, while in fibroblasts the inhibition was almost complete (≥ 99%) similar as shown previously (27). Thus, it is tempting to speculate that a trimer-independent entry mechanism accounts for the residual infectivity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These data are well in line with previous reports showing the inhibitory capacity of sPDGFRα for several distinct HCMV strains (26). Notably, even at a concentration of 1.25μg/ml sPDGFRα we observed a residual infectivity of about 1 - 2% in epithelial cells, while in fibroblasts the inhibition was almost complete (≥ 99%) similar as shown previously (27). Thus, it is tempting to speculate that a trimer-independent entry mechanism accounts for the residual infectivity.…”
Section: Discussionsupporting
confidence: 90%
“…Over the last few years, a number of cellular interaction partners for both, the trimer and the pentamer have been identified (14). One of these cellular receptors, platelet-derived growth factor receptor alpha (PDGFRα), was identified to directly and specifically interact with gO parts of the trimer (2527). This interaction enables entry of cell-free virions into fibroblasts, the only cell type which shows a high PDGFRα expression (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more detail, gH/gL may be complexed either with pUL128L, giving rise to the PC gH/gL/ pUL128L, or UL74-encoded gO, thus forming the trimeric complex gH/gL/gO, which binds to platelet-derived growth factor receptor a and mediates HCMV entry into HELFs [57][58][59]. Thus, gH/gL/gO and PC were considered to represent two mutually exclusive cell entry complexes, as suggested by mass spectrometry and mutagenesis analysis [60].…”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
“…demonstrated that HCMV gB directly interacts with PDGFR-α resulting in receptor tyrosine phosphorylation, indicating that PDGFR-α is a more critical receptor required for HCMV entry than EGFR. Wu et al46 reported that the HCMV glycoprotein complex gH/gL/gO binds to PDGFR-α on the surface of fibroblasts and that gH/gL/gO either directly or indirectly recruits gB to this complex. Additionally, PDGFR-α functions as an entry receptor for HCMV expressing gH/gL/gO, but not for HCMV mutants lacking the gH/gL/gO complex.The EGFR and PDGFR have been shown to perform a similar function and trigger the PI3K/Akt pathway upon virus entry.…”
mentioning
confidence: 99%